ANALISIS KRITIS TERHADAP AKSES PENDIDIKAN DAN PELATIHAN VOKASIONAL BAGI NARAPIDANA PENYANDANG DISABILITAS - Subroto, Mitro; Febriansyah, Rafli Rahmanda Harsanta (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This study critically analyzes the access to vocational education and training for prisoners with disabilities, highlighting the challenges they face in rehabilitation and reintegration into society. The urgency of this research stems from the increasing recognition of the need for inclusive educational opportunities that cater to marginalized groups, particularly those with disabilities within correctional facilities. Employing a qualitative research methodology, data was collected through interviews and document analysis to assess the current state of vocational training programs. The findings reveal significant barriers, including inadequate resources and lack of tailored programs, which hinder effective participation. The study concludes that enhancing access to vocational training is essential for improving employment outcomes and reducing recidivism among disabled prisoners.Keywords: vocational education; prisoners with disabilities; access barriers; rehabilitation; recidivism.